Przemoc seksualna wobec dzieci w okresie pandemii COVID-19: systematyczny przegląd literatury - Ulańska, Patrycja; Orlińska, Aleksandra; Gierczyk, Marcin (Studia Edukacyjne, 2022)
The aim of this article is to review research on child sexual violence during the COVID-19 pandemic. A systematic review procedure based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses protocol was adopted. Analysis of twelve articles published between 2020 and 2022 in peer-reviewed journals showed that social isolation caused by the COVID-19 pandemic contributed to an increase in cases of child sexual violence in developing countries, while it decreased in developed countries. In the articles analyzed, girls were more often the victims of sexual violence during the COVID-19 pandemic than boys.